Leaf and Flower Extracts of Tithonia diversifolia Against Aphis gosypii in Red Chili Plant - Toto Himawan; Tari Rahayu; Tita Widjayanti (University of Brawijaya, 2021)
Red chili is one of the main commodities in Indonesia. Aphid (Aphis gossypii) is one of the pests that cause damage to the red chili plant. A. gossypii attacks require control measures using plant-based pesticides from the leaves and sunflowers of Mexico. This study aimed to determine the toxicity of leaves and flower of T. diversifolia extracts against A. gossypii. This research consisted of five concentrations (0.1, 0.3, 0.5, 0.7 and 0.9%) and four replications. The LC50 and LT50 were calculated by using probit analysis of the Hsin Chi program. The results showed that the Tithonia diversifolia flower extract had higher toxicity than the leaf extract of 0.48%, which could cause the death of A. gossypii by 50%, while the leaf extract had a concentration of 0.55%. The flower extract caused the fastest 50% mortality (37.42 hours), while leaf extract was 65.63 hours. The leaf and flower extracts can also reduce the number of A. gossypii offspring.